Drugs and Conditions That May Mimic Hemolysis: A Case of Pink Plasma. Issue 1 (11th November 2022) - Jones, Andrew D; Sapatnekar, Suneeti; Bakdash, Suzanne
Abstract: Objectives: Visual inspection of posttransfusion plasma for hemolysis is a key laboratory method in the investigation of possible acute hemolytic transfusion reactions (AHTRs). Many substances and physiologic conditions can mimic hemolysis in vitro. Isolated reports describe specific cases of interference, but a comprehensive listing is lacking. Methods: Using an illustrative case, we summarize available literature on substances and conditions that may mimic hemolysis in vitro. We further describe other substances and conditions that may discolor plasma but are unlikely to be mistaken for hemolysis on visual inspection. Results: At least 11 substances and conditions have been reported to discolor plasma, in colors ranging from orange to red to brown, including relatively common therapies (eg, eltrombopag, hydroxocobalamin, iron dextran). Other substances are unlikely to be encountered in everyday practice but may mimic hemolysis in particular patient populations. Additional substances may cause plasma discoloration, ranging from blue to green to white, and are associated with a wide variety of therapies and conditions. Conclusions: An awareness of the possible preanalytic confounding factors that may mimic hemolysis can aid in the workup of a suspected AHTR. Review of the medical record, use of ancillary testing, and consideration for nonimmune causes of hemolysis can aid in ruling out AHTR.